Kendala Pelaksanaan Metode Pembelajaran Kurikulum Merdeka pada Proses Pembelajaran di Sekolah Dasar Negeri - Andriani, Ramandhani Imelia; Widiyono, Aan (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2024)
This study analyzes the obstacles to implementing learning methods by the Independent Curriculum in Public Elementary Schools (SDN). The research method used in this study is descriptive qualitative. The data was collected through interviews with class teachers, classroom observations, and document analysis. The results of this study show three findings. First, there are obstacles in implementing learning methods according to the Independent Curriculum in the form of a need for teacher readiness from designing to implementing the teaching and learning process at SDN 3 Menganti. Second, there is a lack of variation in learning methods used by grade IV teachers of SDN 3 Menganti in the learning process, so they are not in line with students' characteristics and learning interests. Third, the availability of facilities and equipment is inadequate, so implementing the Independent Curriculum in schools is hampered.